Teachers' Strategies and Adaptation Efforts in Addressing the Problems of Implementing the Merdeka Curriculum: A Case Study of State Elementary School 3 Karangampel, Indramayu - Fadilah, Fatin; Putra, Nugraha Permana; Nurkholis, Nurkholis (Jurnal Ragam Pengabdian, 2026)
Teachers implementing Indonesia's Merdeka Curriculum are expected to redesign instruction, assessment, and learning materials almost from scratch, yet little is known about how they actually cope when the necessary support is missing. This case study examines the strategies employed by teachers at State Elementary School 3 Karangampel, Indramayu, in addressing the challenges of curriculum implementation. Data were collected through semi-structured interviews with the principal and three classroom teachers, supplemented by classroom observation and document review, and analyzed using Miles, Huberman, and Saldaña's interactive model. The findings revealed a telling mismatch: the strategies teachers described when asked how they cope turned out to be little more than their everyday teaching methods, such as varying activities, running small group projects, and adjusting to student characteristics, none of which addressed the one problem that mattered most, the absence of any usable teaching module. At the school level, leadership had quietly shifted its support from providing facilities toward building teacher capacity through academic supervision, training, and teacher working-group (KKG) meetings, though whether teachers themselves find this helpful could not be directly confirmed by the study. Teachers' own hopes for the future closely aligned with the problems already identified: more sustained training on module writing, better technology, and a stronger KKG. The gap, then, is not that teachers fail to see what is needed, but that no one has yet turned that shared understanding into a concrete, structured plan of action.